2007
DOI: 10.1080/17450390701664355
|View full text |Cite
|
Sign up to set email alerts
|

Palatability in sheep andin vitronutritional value of dried and ensiled sainfoin (Onobrychis viciifolia) birdsfoot trefoil (Lotus corniculatus), and chicory (Cichorium intybus)

Abstract: Three temperate forages, sainfoin, birdsfoot trefoil, and chicory, characterized by elevated contents of plant secondary compounds, were compared to a ryegrass-clover mixture (control) in dried (Experiment 1) and ensiled form (Experiment 2) in their palatability and nutritional value. Palatability was measured in adult wethers (n = 6) allowed to choose between the familiar control forage and one of the three test plants. Palatability index was calculated from differences in intake of control and test plants me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
58
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 25 publications
10
58
1
4
Order By: Relevance
“…Current study data revealed that the higher fecal N excretion in the presence of active tannins was matched by lower urinary N excretion. This shift can be explained by the lower rumen degradability of nitrogenous compounds and is confirmed by effects of CT on rumen fluid ammonia and total N as previously stated [26,27]. Volatile fatty acids production was not affected by acacia leaves replacement.…”
Section: Discussion Feed Intake and Digestionsupporting
confidence: 55%
“…Current study data revealed that the higher fecal N excretion in the presence of active tannins was matched by lower urinary N excretion. This shift can be explained by the lower rumen degradability of nitrogenous compounds and is confirmed by effects of CT on rumen fluid ammonia and total N as previously stated [26,27]. Volatile fatty acids production was not affected by acacia leaves replacement.…”
Section: Discussion Feed Intake and Digestionsupporting
confidence: 55%
“…In a study by Minnee et al (2002), total condensed tannins in birdsfoot trefoil were not affected by the ensiling process, but free condensed tannins were reduced. This may explain the improvement in palatability of baleage in the current study, although in a study with sheep, Scharenberg et al (2007) did not report an improved palatability for ensiled compared with dried birdsfoot trefoil.…”
Section: Discussioncontrasting
confidence: 74%
“…These findings do not entirely support the assumption that forage species high in secondary compounds reduce voluntary intake because of their bitter taste (Reed, 1995), at least not when offered as baleage. Processing, such as ensiling, has a major effect on structure and chemistry of forages and may change the biological activity of their secondary compounds, as a result of reactions with other plant molecules and fermentation products (Scharenberg et al, 2007). In a study by Minnee et al (2002), total condensed tannins in birdsfoot trefoil were not affected by the ensiling process, but free condensed tannins were reduced.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Forage conservation from hay or silage; maintain the nutritional qualities for long periods of time (Givens & Rulquin, 2004;Scharenberg et al, 2007). In recent years, commercial varieties of triticale and barley have been released, counting on a wide range of advanced lines with specific adaptation to conditions in the highlands of Mexico.…”
Section: Introductionmentioning
confidence: 99%